Pharmacotoxicological properties of prazifen - I. R. Salgiriev; M. B. Musaev (Российский паразитологический журнал, 2016)
Pharmacotoxicological properties of complex anthelmintic prazifen in the form of paste with fenbendazole and praziquantel are investigated. LD50 of prazifen is 7500 mg/kg. Prazifen did not render negative influence on the skin of rats. The preparation has feebly marked cumulation.